Perfil epidemiológico do uso de drogas entre universitários da área da saúde - Tôrres, Ruth (2002)
The psychoactive substance use in the academic universe possesss proper characteristics of this clientele. Objectifying to trace a profile epidemiologist of the psychoactive substance use in the academic universe, this research, of quantitative character, it was applied the 325 academics of the Pharmacy College, Odontologia and Enfermagem of the Federal University of the Ceará. A questionnaire with closed and divided questions at two moments was used: the first one I contend the partner-demographic characterization of the clientele in study and, as the moment with the characterization of the use and frequency of use of the academics in question. The results had been shown through graphical tables and, with return to pertinent literature. As results we have a predominantly feminine sample (66%), with etária band around the 21 years, bachelor (90%), catholics (72%), only students (75%), residents with the parents (78%), with familiar income around 6 the 15 minimum wages, that if optimists (60%) auto-call and with disposal for they capsize the college (66.5%). With regard to the use and frequency of psicotrópicas substance use, the academics make current use of etílicos (30%), tobacco (5.5%) and inalantes (5.5%), marijuana (4%) and cocaine and its derivatives (1%). The use is sporadical of these substances. We conclude that the searched sample corresponds to one terço approach of the academic universe and that the psychoactive substance use is among others related factors with the partner-demographic characterization of the academics. We suggest that the research extends the relative quarrels to the subject, that has the inclusion of this thematic one in the resume, that has campaigns and services of attention directed toward the academic user.